2022
DOI: 10.1111/jocn.16275
|View full text |Cite
|
Sign up to set email alerts
|

Medication reconciliation at hospital discharge: A qualitative exploration of acute care nurses’ perceptions of their roles and responsibilities

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
8
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 45 publications
1
8
0
Order By: Relevance
“…It therefore seems necessary to generate standardized protocols and processes for communication between primary healthcare professionals, and to reduce workloads in consultation to improve care and free up time for professionals to hold coordination meetings, clinical sessions and other activities that improve the exchange of information and teamwork. In fact, teamwork has been identified in our study, and in others [13], as an important facilitator of medication reconciliation in primary healthcare. Other studies showed that a good relationship between healthcare professionals is key to the continuity of care for patients, especially in older adults with polypharmacy and multipathological condition [39,57].…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…It therefore seems necessary to generate standardized protocols and processes for communication between primary healthcare professionals, and to reduce workloads in consultation to improve care and free up time for professionals to hold coordination meetings, clinical sessions and other activities that improve the exchange of information and teamwork. In fact, teamwork has been identified in our study, and in others [13], as an important facilitator of medication reconciliation in primary healthcare. Other studies showed that a good relationship between healthcare professionals is key to the continuity of care for patients, especially in older adults with polypharmacy and multipathological condition [39,57].…”
Section: Discussionsupporting
confidence: 62%
“…However, they do perceive the existence of technologies, such as computerized medical records, as a facilitator, although it seems that even after two decades of its implementation, they are still seen as insufficient mediums for exchanging information. This feeling is enhanced by the fact that the current tool (Diraya) appears to have not improved this communication exchange, given its structure and the display of varied and inexact information based on the healthcare professional's profile, which obliges them to look for new and more precise information [13,29,41,42]. This becomes difficult because the healthcare professionals are already overburdened with work and have little or no time available.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…According to a study done in Australia, more than 60% of nurses think that time constraints and staffing shortages are obstacles to optimal medication reconciliation. 6 …”
Section: Introductionmentioning
confidence: 99%